Peningkatan Kinerja Sumber Daya Manusia melalui Lingkungan Kerja dan Budaya Service Excellence dengan Motivasi sebagai Variabel Intervening (Studi Kasus pada Tanatap Coffee) - Taufik, Yuga; Sumiati, Siti (Lembaga Yasin AlSys, 2026)
Improving human resource performance is an important aspect in the increasingly competitive food and beverage industry, particularly at Tanatap Coffee. The main problem in this context lies in the suboptimal systematic implementation of the work environment and service excellence culture, as well as the lack of structured management of employee motivation. This study aimed to analyze the effect of the work environment and service excellence culture on human resource performance, with motivation as a mediating variable. This study used a quantitative approach with a survey method through the distribution of questionnaires to 94 Tanatap Coffee employees. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. The results showed that the work environment and service excellence culture had positive effects on employees’ work motivation. In addition, the work environment and service excellence culture also had positive effects on human resource performance. Motivation was proven to mediate the effects of the work environment and service excellence culture on employee performance. The conclusion of this study emphasizes that employee performance improvement can be achieved through the creation of a comfortable work environment, the consistent implementation of a service excellence culture, and the continuous strengthening of work motivation. These findings imply the importance of managing the work environment, service culture, and motivation as an integrated strategy for improving human resource performance in the food and beverage industry.